2018
DOI: 10.1051/0004-6361/201732202
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic-ray ionisation in circumstellar discs

Abstract: Context. Galactic cosmic rays (CRs) are a ubiquitous source of ionisation of the interstellar gas, competing with UV and X-ray photons as well as natural radioactivity in determining the fractional abundance of electrons, ions, and charged dust grains in molecular clouds and circumstellar discs. Aims. We model the propagation of various components of Galactic CRs versus the column density of the gas. Our study is focussed on the propagation at high densities, above a few g cm −2 , especially relevant for the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
268
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 167 publications
(290 citation statements)
references
References 79 publications
9
268
1
Order By: Relevance
“…Since the pion rest mass is significant, CR protons lose a non-negligible fraction of their energy in each collision (Schlickeiser, 2002). Padovani et al (2018b) showed that CSDA works for E 25 MeV; according to Fig. 3, this corresponds to column densities N 7 × 10 22 cm −2 .…”
Section: Cosmic-ray Protonsmentioning
confidence: 96%
See 4 more Smart Citations
“…Since the pion rest mass is significant, CR protons lose a non-negligible fraction of their energy in each collision (Schlickeiser, 2002). Padovani et al (2018b) showed that CSDA works for E 25 MeV; according to Fig. 3, this corresponds to column densities N 7 × 10 22 cm −2 .…”
Section: Cosmic-ray Protonsmentioning
confidence: 96%
“…Thus, we adopt the concept of the guiding centre for CRs and consider their propagation along the local magnetic field, with coordinate s measured along the field line. We introduce the effective column density of gas traversed by a CR particle before it reaches a given point (Padovani et al, 2018b),…”
Section: Transport and Penetration Of Crs Into Dense Astrophysical Obmentioning
confidence: 99%
See 3 more Smart Citations